P-57 Attitudes and issues encountered during communication of end-of-life care decisions in a south-east asian (SEA) heart failure patient cohort. (1st September 2015) - Ng, Clarice SH; Lau, Cindy SL; Wong, Jane CQ; Tan, BC; Wong, G; Sim, KLD; Chetna, M
Abstract : Background: Limited data on the factors affecting end-of-life (EOL) decisions faced by heart failure patients in a SEA population. Aim: Identify attitudes and issues heart failure patients face with communication of EOL decisions in a SEA population. Methods: A qualitative study was conducted with five focus group sessions (N = 27), 5–6 heart failure per session, over a six month period. Results: The qualitative study revealed six themes representing the issues that heart failure patients faced: 1) physical and psychological symptoms; 2) financial concerns; 3) uncertainty and lack of knowledge about the disease; 4) difficulties in navigating the healthcare system; 5) EOL care concerns; and, 6) fear of being a burden to the family. Discussion: Out of the six themes raised, points 3, 5 and 6 are areas that can be addressed with Advance Care Planning (ACP). The results show that patients want autonomy and more information about their treatment options so as to resolve EOL care issues and reduce family burden. In contrast to those without ACP, patients who underwent ACP discussion were clearer on their treatment preferences and had discussion on EOL decisions with their physicians and family members. Conclusion: There is inadequate discussion between the healthcare providers and the patients regarding treatment plans, expected side effects and prognosis in our current healthcare system. Having an ACP program will facilitate a patient-centric and proactive approach towards engaging patients and their families on EOL issues.